Bone histomorphometry of the clavicle in a forensic sample from Albania. (August 2020) - Kranioti, Elena F.; Michopoulou, Effrosyni; Tsiminikaki, Konstantina; Bonicelli, Andrea; Kalochristianakis, Michalis; Xhemali, Bledar; Paine, Robert R.; García-Donas, Julieta G.
Highlights: Age estimation on the clavicle using histomorphometry has been only performed on four populations. None of the existing histological methods provided accurate age estimates for the Albanian sample. Population-standards for estimating histological age on the sample under study is deemed to be feasible. Bone remodelling differences between Albanian and Americans are reported. Abstract: Forensic assessment of skeletal material includes age estimation of unknown individuals. When dealing with extremely fragmented human remains that lack macro-features used in age estimation, histological assessment of the skeletal elements can be employed. Historically, microscopic methods for age assessment used by forensic anthropologists have been available since 1965. Several skeletal elements have been used for this purpose. Among them, the clavicle has garnered very little attention. The purpose of this study is to explore the validity of clavicular histomorphometry as an age marker in a modern Balkan sample. This study examined a modern clavicular autopsy sample from Albania. The sample consisted of 33 individuals of known age and cause of death. Data were collected for micro-anatomical features including osteon population density (OPD) and cortical area. Intra- and inter-observer errors were assessed through technical error of measurement (TEM) and R coefficient. A validation study was performed in order to test the accuracy of existing histological formulae. Regression analysis was run to developed age prediction models with the best models tested through cross-validation and the comparison between OPD for the Albanian sample and a European–American sample examined. Intra- and inter-observer error TEM results demonstrated values falling within the limits of acceptance. The existing histological methods did not perform accurately on the sample under study. Regression equations for Albanians produced age estimations deviating 8 and 11 years from known age. Cross-validation on the most accurate regression formula which includes OPD as a single variable demonstrated similar mean errors. Statistically significant differences were observed between the Albanian and the European–American population when the two samples were compared. The research presented is the fifth article published and the fifth population explored on clavicular microstructure. The potential of histology to estimate age on the Albanian population is shown here; however, population effect, diet and health status might be considered. Further inclusion of individuals will corroborate our preliminary findings.